KAJIAN KUALITATIF GAYA KEPEMIMPINAN DAN MODEL BISNIS INOVATIF PT.BUKALAPAK STARTUP UNICORN INDONESIA - Ferawaty Usman; Djabir Hamzah; Fauziah Umar (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2019)
This study aims to 1) to know the leadership style owned by CEO Bukalapak 2) to know the innovative business model implemented by CEO Bukalapak 3) to know whether leadership style owned by CEO Bukalapak according to business model applied. The method used is Qualitative research method. The types and sources of data used are primary and secondary data. Informants / sources are selected from the Internal and External PT.Bukalapak as many as 12 people informants. Data collection techniques conducted in this study are Observation, Interview and Documentation Technique. Data in the analysis by using qualitative descriptive data analysis techniques. The results of this study indicate that leadership style owned by CEO Bukalapak is Visionary leadership style and leadership style Partisipatif. The business model implemented in Bukalapak is Marketplace Customer to Customner (C2C) based on E-Commerce. Leadership style owned by CEO of Bukalapak according to business model applied.